2016
DOI: 10.3390/catal6070092
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts for the Selective Oxidation of Methanol

Abstract: Abstract:In industry, one of the main catalysts typically employed for the selective oxidation of methanol to formaldehyde is a multi-component oxide containing both bulk Fe 2 (MoO 4 ) 3 and excess MoO 3 . It is thought that the excess MoO 3 primarily acts to replace any molybdenum lost through sublimation at elevated temperatures, therefore preventing the formation of an unselective Fe 2 O 3 phase. With both oxide phases present however, debate has arisen regarding the active component of the catalyst. Work h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 63 publications
1
45
0
Order By: Relevance
“…In order to determine which factors affect the active species for methanol selective oxidation on iron molybdate catalysts, Brookes et al [10][11][12][13] have studied this catalytic system extensively. It was concluded that selective oxidation of methanol depends on the presence of a molybdenum oxide dominated surface layer.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine which factors affect the active species for methanol selective oxidation on iron molybdate catalysts, Brookes et al [10][11][12][13] have studied this catalytic system extensively. It was concluded that selective oxidation of methanol depends on the presence of a molybdenum oxide dominated surface layer.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the study of the reactivity of biomass on oxide surfaces has many more fundamental problems arising from the complexity of the electronic structure of these materials but also for the much wider variability in the types of elementary steps that they allow. For instance, ceria and molybdenum oxides have been described as active in the transformation of methanol (a byproduct of several biomass conversion processes) into formaldehyde . For CeO 2 , the structure sensitivity drives the selectivity: the closed‐packed (111) and (110) surfaces produce formaldehyde, which on the (100) surface is further oxidized to CO .…”
Section: Introductionmentioning
confidence: 99%
“…Demand for formaldehyde is increasing, and currently exceeds 30 MT/year [1], while demand for acetaldehyde is around 1 MT/year, while unregenerable catalysts are unable to support these requirements. Recently, considerable interest is being paid to the dehydrogenation of methanol and ethanol due to the safety and sustainability aspects of the reaction compared to the oxidative route.…”
Section: Introductionmentioning
confidence: 99%